Innovative Diagnostic Approaches for TORCH Infections in Pregnancy: The Role of IgG Avidity and Affinity-Switchable Lateral Flow Assays - Fauziah, Dina (Jurnal KESANS : Kesehatan dan Sains, 2025)
Abstract Background: TORCH infections (Toxoplasma gondii, “Others,” Rubella virus, Cytomegalovirus, and Herpes simplex virus) are responsible for 2–3% of congenital anomalies worldwide and remain a significant cause of miscarriage, stillbirth, and lifelong disability. Early and accurate diagnosis is critical, yet conventional methods—serology and PCR—are costly, infrastructure-dependent, and often inaccessible in low-resource settings. Objective: This narrative review evaluates current TORCH diagnostic approaches and explores the potential of Affinity-Switchable Lateral Flow Assays (ASLFA), with emphasis on adapting the technology for IgG avidity testing to improve maternal screening. Content: Conventional serology provides information on IgM and IgG status but cannot reliably differentiate acute from past infections. IgG avidity testing refines interpretation, particularly for CMV and toxoplasmosis, by distinguishing recent primary infections from reactivations. However, avidity assays are laboratory-based and unavailable in many regions. ASLFA introduces a conditional “signal-on” design, expanding LFA utility to small molecules and functional readouts. Incorporating chaotropic reagents into ASLFA strips could enable on-site avidity measurement, while pathogen-specific antigens, such as CMV glycoprotein B (CMV34), may enhance specificity. Conclusion: ASLFA platforms integrating IgG avidity offer a promising, low-cost, point-of-care alternative to conventional tests. With further validation, they could democratize TORCH screening and improve maternal–fetal outcomes, particularly in resource-limited settings.